Natal and neonatal care practices of recently-delivered woman in rural areas of Lucknow district - Yadav, Arun; Gupta, Pratibha; Srivastava, Mrinal Ranjan; Zaidi, Zeashan Haider (International Journal Of Community Medicine And Public Health, 2019)
Background: The health of women and children are eternally linked and when the health of women and child improves, life improves by every measure. Deaths associated with child birth were so common that societies developed cultural coping strategies or traditional practices. The objective of the study is to assess natal and neonatal care practices in rural areas of Lucknow district. Methods: The present study was carried out in the rural areas of Lucknow district. Study unit was recently delivered women (RDW), who gave birth to live newborn in last 1 year in rural areas of Lucknow for a period of 12 months. It was community based cross sectional study. A total of 368 RDW were interviewed. Multi stage random sampling technique was used to select RDW. Results: Majority cited all the reasons for preferring institutional delivery (58.2%) followed by those citing it cheaper or better services (17.4%) each and incentive (7.4%) respectively. Weight of baby was 2.5 to 3.5 kg in maximum cases (88%) followed by <2.5 kg (10.3%) respectively. Majority did not have any complication at birth (87%). Exclusive breast feeding was reported by majority (81%). Conclusions: Community needs to be appraised regarding performance and important positive achievement of MCH services in relation to health status of mother and neonate in their respective areas through community participation and will make the community more respective towards availing of accredited social health activist (ASHA) services. Proper provisioning of auxiliary nurse midwiferys, ASHAs and lady health workers would facilitate improvements in rural areas.